POLEMIK â€œAHLI BIDâ€™AHâ€ DALAM WACANA ULÅªMUL HADÄªá¹ : Evaluasi Ibnu á¸¤ajar al-â€˜AsqalÄny Terhadap Status RiwÄyat al-Mubtadiâ€™ - Asep Nahrul Musadad dan Ismangil Ngarfillah (IAIN Kediri, 2016)
AbstractOne of the key terms employed in showing the connection between jarh wa taâ€™dÄ«l discourse and Islamic sectarianism issues is bidâ€™ah â€œheresyâ€ and al-mubtadiâ€™ â€œheretic transmitterâ€. Start on preliminary introduction to bidâ€™ah conception in the context of jará¸¥ wa taâ€™dÄ«l, this article discusses Ibn á¸¤ajar al-â€˜AsqalÄniâ€™s notions about the concept of heresy (bidâ€™ah) and validity of heretic transmitter (riwÄyat al-mubtadiâ€™). Ibá¹‡ Hajar was choosed here as the exponent of culmination in â€œulÅ«m al-hadÄ«tá¸£â€ discourse in which the bidâ€™ah notion was arguably reconsidered along with the still-functioning Islamic sectarianism polemic. It deals finally with â€œkafirâ€ claims (takfÄ«r) as the so-called â€œtheological weaponâ€ to blame others.Keywords; Ibnu Hajar al-â€˜AsqalÄni, bidâ€™ah, dan riwÄyat al-mubtadiâ€™